Solubility of CO2 in aqueous piperazine and its modeling using the Kent-Eisenberg approach - Aroua, Mohamed Kheireddine; Salleh, R.M. (Wiley, 2004)
A systematic investigation of the equilibrium solubility of CO2 in aqueous piperazine solutions was conducted in a double-jacketed stirred cell reactor. The solubilities of CO2 in the solution were measured at 20, 30, 40, and 50 Â°C with CO2 partial pressures ranging from 0.4-95 kPa. Generally the aqueous piperazine solution exhibits the same characteristics as conventional alkanolamines. Increasing the CO2 partial pressure increases the gas loading, however increasing the temperature or concentration decreases the CO2 loading. The values of the CO2 loading obtained confirm that the piperazine forms stable carbamates. The equilibrium solubility data were analyzed using a Kent-Eisenberg approach. Representation of the model is generally in good agreement with that of the experimental data, especially at high temperature.